Transcriptional Activity of Predominant Streptococcus Species at Multiple Oral Sites Associate With Periodontal Status - Belstrøm, Daniel; Constancias, Florentin; Markvart, Merete; Sikora, Martin; Sørensen, Christiane Elisabeth; Givskov, Michael (Frontiers in Cellular and Infection Microbiology, 2021)
Background Streptococcus species are predominant members of the oral microbiota in both health and diseased conditions. The purpose of the present study was to explore if different ecological characteristics, such as oxygen availability and presence of periodontitis, associates with transcriptional activity of predominant members of genus Streptococcus. We tested the hypothesis that genetically closely related Streptococcus species express different transcriptional activities in samples collected from environments with critically different ecological conditions determined by site and inflammatory status. Methods Metagenomic and metatranscriptomic data was retrieved from 66 oral samples, subgingival plaque (n=22), tongue scrapings (n=22) and stimulated saliva (n=22) collected from patients with periodontitis (n=11) and orally healthy individuals (n=11). Species-specific transcriptional activity was computed as Log2(RNA/DNA), and transcriptional activity of predominant Streptococcus species was compared between multiple samples collected from different sites in the same individual, and between individuals with different oral health status. Results The predominant Streptococcus species were identified with a site-specific colonization pattern of the tongue and the subgingival plaque. A total of 11, 4 and 2 pathways expressed by S. parasanguinis, S. infantis and S. salivarius, respectively, were recorded with significantly higher transcriptional activity in saliva than in tongue biofilm in healthy individuals. In addition, 18 pathways, including pathways involved in synthesis of peptidoglycan, amino acid biosynthesis, glycolysis and purine nucleotide biosynthesis expressed by S. parasanguinis and 3 pathways expressed by S. salivarius were identified with significantly less transcriptional activity in patients with periodontitis. Conclusion Data from the present study significantly demonstrates the association of site-specific ecological conditions and presence of periodontitis with transcriptional activity of the predominant Streptococcus species of the oral microbiota. In particular, pathways expressed by S. parasanguinis being involved in peptidoglycan, amino acid biosynthesis, glycolysis, and purine nucleotide biosynthesis were identified to be significantly associated with oral site and/or inflammation status.